Portal vein thrombosis compromises the performance of MELD and MELD‐Na scores in patients with cirrhosis. Issue 1 (25th November 2022) - Ouyang, Renjie; Li, Hai; Tan, Wenting; Wang, Xianbo; Zheng, Xin; Huang, Yan; Meng, Zhongji; Gao, Yanhang; Qian, Zhiping; Liu, Feng; Lu, Xiaobo; Shi, Yu; et al.
Abstract: Background and Aims: The accuracy of model for end‐stage liver disease (MELD) and MELD with sodium (MELD‐Na) scores in reflecting the clinical outcomes of patients with cirrhosis and portal vein thrombosis (PVT) remains unclear. This study aimed to evaluate the performance of scores in predicting 90‐day mortality in patients with cirrhosis and PVT. Methods: Post hoc analysis was performed in two prospective cohorts (NCT02457637 and NCT03641872). The correlation between the MELD/MELD‐Na score and 90‐day liver transplantation (LT)‐free mortality was investigated in patients with cirrhosis with and without PVT. Results: In this study, 2826 patients with cirrhosis were included, and 255 (9.02%) had PVT. The cumulative incidence of 90‐day LT‐free mortality did not significantly differ between patients with and without PVT (log‐rank P  = 0.0854). MELD [area under the receiver operating curve (AUROC), 0.649 vs. 0.842; P  = 0.0036] and MELD‐Na scores (AUROC, 0.691 vs. 0.851; P  = 0.0108) were compared in patients with and without PVT, regarding the prediction of 90‐day LT‐free mortality. In MELD < 15 and MELD‐Na < 20 subgroups, patients with PVT had a higher 90‐day LT‐free mortality than those without PVT (7.91% vs. 2.64%, log‐rank P  = 0.0011; 7.14% vs. 3.43%, log‐rank P  = 0.0223), whereas in MELD ≥ 15 and MELD‐Na ≥ 20 subgroups, no significant difference was observed between patients with and without PVT. Conclusions: The performance of MELD and MELD‐Na scores in predicting 90‐day LT‐free mortality of patients with cirrhosis was compromised by PVT. MELD < 15 or MELD‐Na < 20 may underestimate the 90‐day LT‐free mortality in patients with PVT.